The Phenomenon of Sleep Call from the Perspective of the Prophet's Hadith - Sarmilah, Sarmilah; Hasanah, Uswatun; Zulfikar, Eko (Diroyah : Jurnal Studi Ilmu Hadis, 2023)
This article examines the sleep call phenomenon as the beginning of adultery with a focus on studying the hadiths about adultery. By using a qualitative descriptive-analytical type of library research, this article draws the following conclusions; First, the understanding of hadiths about adultery shows that adultery is not only interpreted as having intimate relations between men and women, but adultery includes a broad meaning that can lead to the true meaning of adultery, such as adultery of the eyes, adultery of the ear, adultery of the hands, adultery heart, and so on. Second, the sleep call phenomenon that is currently happening especially among teenagers, with reference to the understanding of hadiths about adultery, is an act that can approach adultery and the beginning of adultery. Explanation of the Prophet's hadith which shows that many things can approach true adultery, such as ear adultery, tongue adultery, hand adultery, and heart adultery, can position the sleep call phenomenon as including actions that are close to adultery so that it can lead to true adultery, namely having sex between men -male and female.